Assessing the Likelihood of Hand-to-Hand Cross-Transmission of Bacteria: An Experimental Study. (22nd February 2017) - Bellissimo-Rodrigues, Fernando; Pires, Daniela; Soule, Hervé; Gayet-Ageron, Angèle; Pittet, Didier
Abstract : BACKGROUND: Although the hands of healthcare workers (HCWs) are implicated in most episodes of healthcare-associated infections, the correlation between hand contamination and the likelihood of cross-transmission remains unknown. METHODS: We conducted a laboratory-based study involving pairs of HCWs. The hands of a HCW (transmitter) were contaminated with Escherichia coli ATCC 10536 before holding hands with another HCW (host) for 1 minute. Meanwhile, the unheld hand of the transmitter was sampled. Afterward, the host's held hand was also sampled. Each experiment consisted of 4 trials with increasing concentrations of E. coli (10 3 –10 6 colony-forming units [cfu]/mL). The primary outcome was the likelihood of transmission of at least 1 cfu from transmitter to host. We used a mixed logistic regression model with a random effect on the subject to assess the association between transmission and bacterial count on the transmitter's hands. RESULTS: In total, 6 HCWs performed 30 experiments and 120 trials. The bacterial counts recovered from host hands were directly associated with the bacterial counts on transmitter hands ( P <.001). The probability of cross-transmission was 8.22 higher (95% confidence interval [CI], 0.98–68.8) when transmitter hand bacterial count was >1 and ≤3 log10 cfu compared to ≤1 log10 . When transmitter contamination was <1 log10 cfu, no cross-transmission was detected. CONCLUSION: There is a direct relationship between the bacterial burden on HCWs hands and the likelihood of cross-transmission. Under the described conditions, at least 1 log10 cfu must be present on HCW hands to be potentially transmitted. Further studies are needed at the low contamination range. Infect Control Hosp Epidemiol 2017;38:553–558